Minimally invasive surgery in women with endometrial cancer on haemodialysis: a tertiary centre experience - Tan, Y. H.; Siew, Shayna J. Y.; Yap, Jeannie J. Y.; Ravichandran, N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
The aim of the case series was to determine if minimally invasive approach to cancer staging is safe and feasible for patients on haemodialysis. We looked at patients on haemodialysis with endometrial cancer who underwent minimally invasive hysterectomy bilateral salpingo-oophorectomy with pelvic lymph node dissection performed by the Gynaecological Oncology unit at Singapore General Hospital from 2016 to 2020. Their demographics, operative details, oncological outcomes, and any post-operative complications were recorded. A total of 16 haemodialysis patients undergoing either laparoscopic or robotic endometrial cancer staging were selected. In our case series, mean duration of surgery was 173 minutes. Mean post-operative high dependency unit stay was 1 day with mean total length of hospitalisation of 5 days. All patients were ambulant at 24 hours post-surgery with pain scores peaking at 2 out of 10 at 6 hours post-surgery, and declining to 0 at 12 hours post-surgery. None of the patients experienced post-operative fluid dysfunction, electrolyte imbalance, sepsis, venous thromboembolism, cardiovascular or wound related complications. We conclude that minimally invasive surgical techniques is a safe and viable approach to endometrial cancer staging for patients on haemodialysis. Further refinement and streamlining of various strategies in the pre-, intra-, and post-operative period can further improve patient outcomes and quality of care.